Polymer composition
By using starch of polysaccharide components and controlling their molecular structure, self-crosslinking of polymer compositions is achieved, and the problem of existing SAP being difficult to degrade after being discarded is solved, and materials with excellent absorption capacity and biodegradability are obtained.
Patent Information
- Application Number
- CN202380059392.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-25
AI Technical Summary
Existing superabsorbent polymers (SAPs) are difficult to degrade after being discarded, resulting in environmental pollution while also being difficult to maintain excellent absorption capacity and physical properties in biodegradable materials.
By using polysaccharide components, especially starch, as the main component of the polymer composition, and by controlling the ratio of amylopectin and the molecular weight of the polysaccharide components, self-crosslinking of the polymer composition is achieved, thereby obtaining materials with excellent absorption capacity and biodegradability.
The balance between absorption capacity and biodegradability of polymer compositions is achieved, providing an environmentally friendly solution suitable for a variety of application scenarios.
Smart Images

Figure CN119698445A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0110608, filed on September 1, 2022, the disclosure of which is incorporated herein by reference in its entirety.
[0002] The present application relates to polymer compositions and uses thereof. Background Art
[0003] A hydrogel polymer or hydrogel is generally defined as a hydrophilic polymer that has been cross-linked.
[0004] Such polymers can be used as materials called SAP (Super Absorbent Polymer). SAP is a material that can absorb tens to thousands of times its own weight of water. SAP is used in various applications, such as sanitary products such as sanitary products or diapers, medical products, household materials, agricultural materials, gardening materials, transportation materials, civil engineering and construction materials, materials related to electrical and electronic equipment, or water treatment agents.
[0005] The most widely used hydrogel polymers for use as SAPs are polymers made from vinyl-based materials, such as cross-linked polyacrylic acid.
[0006] Such a material is relatively inexpensive and has excellent water absorption capacity, but it causes various problems because it remains semi-permanently even after being discarded.
[0007] In order to solve such problems, various attempts have been made to manufacture SAP from so-called biodegradable materials.
[0008] However, materials known so far cannot form SAPs with balanced physical properties. For example, the most representative physical property required for SAP is absorption capacity, but in SAPs of biodegradable materials known so far, at least one of absorption capacity and biodegradability cannot be satisfactorily ensured, or in some cases, both physical properties cannot be ensured at appropriate levels. Summary of the invention
[0009] Technical issues
[0010] The present application aims to provide a polymer composition capable of simultaneously ensuring excellent absorption capacity and biodegradability and use thereof.
[0011] Technical Solution
[0012] Unless otherwise specifically stated, among the physical properties mentioned in this specification, the values of the physical properties affected by the measurement temperature are the results of measurement at room temperature.
[0013] In the present specification, the term room temperature is a natural temperature without artificial heating and cooling, and may mean, for example, any temperature within a range of about 10°C to 30°C, or a temperature around 23°C or 25°C.
[0014] Unless otherwise specifically stated, among the physical properties mentioned in this specification, the values of the physical properties affected by the measurement pressure are the results of measurement under normal pressure.
[0015] In the present specification, the term normal pressure is a pressure around general atmospheric pressure without artificial pressurization or decompression, which may mean, for example, a pressure around about 740 mmHg to 780 mmHg.
[0016] Unless otherwise specified, among the physical properties mentioned in this specification, the values of the physical properties affected by the measured humidity are the results of measurement under the humidity of the standard state.
[0017] In this specification, the humidity in a standard state means a humidity of about 40%, 50%, or 60% as a relative humidity.
[0018] In this specification, unless otherwise stated, the term alkyl or alkyl group means an alkyl or alkyl group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms. Such an alkyl or alkyl group can be linear, branched or cyclic. Such an alkyl or alkyl group can also be optionally substituted with one or more substituents.
[0019] In this specification, unless otherwise indicated, term alkylene or alkylene group means the functional group that is connected to other object by separating two hydrogen atoms from alkane, wherein it has the structure of separating two hydrogen atoms from the different carbon atoms of alkane.Such alkylene or alkylene group can be alkylene or alkylene group with 2 to 20 carbon atoms, 2 to 16 carbon atoms, 2 to 12 carbon atoms, 2 to 8 carbon atoms or 2 to 4 carbon atoms.Such alkylene or alkylene group can be linear, branched or cyclic.Such alkylene or alkylene group also can optionally replace through one or more substituents.
[0020] In this specification, unless otherwise indicated, the term alkylidene or alkylidene group means a functional group connected to another object by separating two hydrogen atoms from an alkane, wherein it has a structure that separates two hydrogen atoms from one carbon atom of an alkane. Such an alkylidene or alkylidene group can be an alkylidene or alkylidene group with 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms or 1 to 4 carbon atoms. Such an alkylidene or alkylidene group can be linear, branched or cyclic. Such an alkylidene or alkylidene group can also optionally be substituted through one or more substituents.
[0021] In the present specification, the term hydrogel polymer or hydrogel polymer composition may mean an absorbent material containing a polymer, and such a material may also be simply referred to as a hydrogel.
[0022] In the present specification, the term absorbent material means a material that exhibits at least one property of water content, centrifuge retention capacity (CRC) and absorption capacity under pressure (AUP) as defined in the present specification.
[0023] In this specification, a biodegradable material means a material that exhibits a certain degree of biodegradability as defined herein.
[0024] The present application relates to polymer compositions. The polymer compositions may be both absorbent and biodegradable materials as described above.
[0025] In this specification, the term polymer composition means a material comprising a polymer. Here, the term composition means a material comprising two or more components. In this case, the two or more components do not necessarily have to be components of different types. For example, the polysaccharide component to be described below can be composed of a polysaccharide polymer having two or more molecules, and in this case, even if only the polysaccharide component is present, the related material can also be referred to as a polymer composition. In addition, the two or more components contained in the polymer composition can interact or react physically or chemically with each other, or can also be in a state of simple mixing without such interaction or reaction. Polymer can mean a material formed by connecting two or more unit bodies by covalent bonds. In an example, a polymer can be a material comprising a structure in which two or more unit bodies are connected by covalent bonds and having a molecular weight greater than or equal to a certain level. The range of molecular weight is not limited, but in terms of weight average molecular weight (Mw), the molecular weight of the polymer can be about 500g / mol or more. The upper limit of the weight average molecular weight is not particularly limited, for example, the weight average molecular weight of the polymer can be about 1,000,000g / mol or less.
[0026] The weight average molecular weight is a value measured by the method described in "4. Measurement of Molecular Weight of Polysaccharide Component" in the Example section in the present specification.
[0027] In one example, the lower limit of the polymer content in the polymer composition can be about 55 weight %, 60 weight %, 65 weight %, 70 weight %, 75 weight %, 80 weight %, 85 weight %, 90 weight %, or 95 weight %, and its upper limit can be about 100 weight %, 100 weight %, 98 weight %, 96 weight %, 94 weight %, 92 weight %, or 90 weight %. The content can also be greater than or equal to, or greater than any one of the above lower limits; or less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. The content of the polymer is based on the solid content, and therefore, when the polymer composition includes a solvent, the content is a ratio relative to the weight of the entire polymer composition excluding the solvent.
[0028] The polymer composition may comprise a polysaccharide component.
[0029] The term polysaccharide component means a component consisting of one or more polysaccharides. That is, the polysaccharide component contains only polysaccharides. The polysaccharides contained in the polysaccharide component can be one or two or more types. Here, the category of two or more polysaccharides can also include polysaccharides with different chemical structures (e.g., different types of repeating units, etc.) and / or polysaccharides with the same or substantially similar chemical structures but different physical properties such as molecular weight.
[0030] The term polysaccharide has a meaning known in the industry. Polysaccharides generally refer to polymer molecules in which two or more unit bodies are linked by covalent bonds. Here, in one example, the covalent bonds linking the unit bodies may be glycosidic bonds. Polysaccharides are polymer molecules, i.e. polymers, which may have a weight average molecular weight within the above range.
[0031] The unit body forming the polysaccharide can be a biomolecule composed of carbon, hydrogen and oxygen, or composed of carbon, hydrogen, oxygen and nitrogen. In this specification, the term biomolecule is interpreted as having the meaning commonly used in industry. Typically, as an example of a biomolecule in industry, monosaccharides such as glucose, galactose, fructose or xylose are known; disaccharides such as sucrose, lactose, maltose or trehalose; polyols such as sorbitol or mannitol; oligosaccharides such as maltodextrin, dextrin, raffinose, stachyose or oligofructose; and / or amino sugars such as glucosamine or N-acetylglucosamine; etc., but the types of biomolecules used in this application are not limited to the aforementioned.
[0032] In one example, the polymer composition may also be in a powder or granule state formed by a grinding process or the like.
[0033] The polymer composition may contain only the polysaccharide component, or may further contain other components in addition to the polysaccharide component as a polymer. In the polymer composition, the polysaccharide component may be present in a cross-linked state.
[0034] Examples of other components that may be included in the polymer composition together with the polysaccharide are not particularly limited, but a cross-linking agent that cross-links the polysaccharide, a polymer different from the polysaccharide, and the like may be exemplified.
[0035] In one example, the weight ratio of the polysaccharide component in the polymer composition can have a lower limit of about 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%, 94%, 96%, or 98% by weight, and an upper limit thereof can be about 100%, 98%, 96%, 94%, 92%, or 90% by weight. The weight ratio can also be in a range of greater than or equal to, or greater than any one of the above lower limits; or in a range of less than or equal to, or less than any one of the above upper limits while being greater than or equal to, or greater than any one of the above lower limits. The weight ratio is a ratio based on solid content, and therefore, when the polymer composition includes a solvent, the ratio is a ratio relative to the weight of the entire polymer composition excluding the solvent.
[0036] The higher the ratio of the polysaccharide component in the polymer composition, the higher the biodegradability of the polymer composition. By applying a specific type of polysaccharide component as the polysaccharide component, appropriate cross-linking can be performed, and the cross-linked material can simultaneously exhibit excellent absorption capacity and biodegradability.
[0037] When the polymer composition is an absorbent material, the lower limit of the water content of the polymer composition can be about 40 wt%, 45 wt%, 50 wt% or 55 wt%, and the upper limit thereof can be about 70 wt%, 65 wt% or 60 wt%. The water content can also be in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0038] The water content is the content ratio of the water contained in the polymer composition relative to the total weight of the polymer composition to be measured, which can be calculated by the weight of the polymer composition containing water and the weight of the dried polymer composition. For example, the water content can be calculated by the weight loss caused by the evaporation of water in the polymer composition during the process of drying the polymer composition in a crumb state by infrared heating. The drying process for measuring the water content may include raising the temperature from room temperature to about 50°C, and then vacuum drying for about 6 hours while maintaining 50°C. The polymer composition may show the water content before or after cross-linking.
[0039] When the polymer composition is an absorbent material, the lower limit of the centrifuge retention capacity (CRC) of the polymer composition according to EDANA (European Disposables and Nonwovens Association) method WSP241.3 can be about 12g / g, 13g / g, 14g / g, 15g / g, 20g / g, 25g / g, 30g / g, 35g / g, 40g / g, or 45g / g, and the upper limit thereof can be about 60g / g, 55g / g, 50g / g, 45g / g, 40g / g, 35g / g, 34g / g, 33g / g, or 32g / g. The centrifuge retention capacity can also be in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits while being greater than or equal to, or greater than any one of the above lower limits. The centrifuge retention capacity was evaluated by the method described in "1. Evaluation of Centrifuge Retention Capacity (CRC)" of the Example section in this specification. The polymer composition may exhibit the centrifuge retention capacity before or after cross-linking.
[0040] When the polymer composition is an absorbent material, the polymer composition can have an absorption capacity under pressure (AUP) at 0.7 psi according to EDANA (European Disposables and Nonwovens Association) method WSP 242.3 of about 1.5 g / g, 2 g / g, 2.5 g / g, 3 g / g, 3.5 g / g, 4 g / g, 4.5 g / g, 5 g / g, or 5.5 g / g, and an upper limit thereof can be about 40 g / g, 35 g / g, 30 g / g, 20 g / g, 15 g / g, 10 g / g, 8 g / g, 6 g / g, or 4 g / g. The absorption capacity under pressure can also be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits while being greater than or equal to, or greater than any of the above lower limits. The absorption capacity under pressure is evaluated by the method described in "2. Evaluation of absorption capacity under pressure (AUP)" of the Example section in the present specification. The polymer composition may exhibit the absorption capacity under pressure before or after crosslinking.
[0041] If the polymer composition exhibits at least one of the properties of water content, centrifuge retention capacity and absorption capacity under pressure as described above, the material in question may be defined as an absorbent material.
[0042] The polymer composition may exhibit excellent biodegradability. For example, the polymer composition may be an absorbent material and may also be a biodegradable material. For example, the lower limit of the biodegradability of the polymer composition may be about 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98% or 99%, and the upper limit thereof may be about 100%, 98%, 96%, 94%, 92%, 90%, 88%, 86%, 84%, 82%, 80%, 78% or 76%. The biodegradability may also be within a range greater than or equal to, or greater than any of the above lower limits; or within a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The biodegradability is evaluated by the method described in "3. Measurement of biodegradability" of the Example section in the present specification. The polymer composition may exhibit the biodegradability before or after cross-linking.
[0043] The polymer composition can simultaneously exhibit excellent absorbency and biodegradability.
[0044] Such a polymer composition can be achieved by applying a polysaccharide component to be described below as a polysaccharide component. Generally, a polysaccharide-based polymer composition has excellent biodegradability, but has low water absorption capacity and low crosslinking efficiency for application as an absorbent material. Therefore, generally, in order to form an absorbent material using a polysaccharide-based material, it is obtained by blending other components with the polysaccharide, rather than applying only the polysaccharide. However, when a specific type of polysaccharide component is applied as the polysaccharide component, only the polysaccharide component can ensure an effective crosslinking rate to be described below, and can simultaneously exhibit excellent absorption capacity and biodegradability after crosslinking.
[0045] As described above, the polysaccharide is a polymeric substance in which two or more units are linked by a covalent bond such as a glycosidic bond, and representative known polysaccharides include starch, dextrin, chitosan, and the like.
[0046] The polysaccharide component may include one or more selected from starch, dextrin and chitosan.
[0047] In one example, the polysaccharide component can include amylose and amylopectin.
[0048] Amylopectin and amylose are types of polysaccharides mainly found in plants, and starch of polysaccharides is composed of amylose and amylopectin. Amylose is composed of glucose molecules linked by α(1→4) glycosidic bonds and has a linear chain structure, while amylopectin has relatively short and highly branched chains. Compared with amylopectin, amylose is relatively easy to crystallize, and amylopectin has relatively higher solubility in water than amylose.
[0049] In the present specification, it was determined that the ratio of amylose to amylopectin in the polysaccharide component and the molecular weight of the associated polysaccharide component significantly correlated with the absorption capacity and biodegradability of the polymer composition.
[0050] As the ratio of amylopectin in the polysaccharide component decreases and the ratio of amylose increases, the biodegradability of the material increases, but the absorption capacity tends to decrease to some extent. In addition, as the molecular weight of the polysaccharide component increases, the biodegradability of the material decreases, but the absorption capacity tends to increase. Therefore, by controlling the amount of amylose and amylopectin and the molecular weight of the polysaccharide component, a material with excellent biodegradability and absorption capacity can be obtained.
[0051] Therefore, F according to the following Equation 1 of the polymer composition may be within a predetermined range.
[0052] [Equation 1]
[0053]
[0054] In Equation 1, Ap is the ratio of amylopectin in the polysaccharide component, Am is the ratio of amylose in the polysaccharide component, and Mw is the weight average molecular weight of the polysaccharide component.
[0055] F in equation 1 is a factor determined based on the relationship between the amount of amylose and amylopectin in the polysaccharide component and the molecular weight of the polysaccharide component. For example, the value of F above increases as the molecular weight of the polysaccharide component increases and / or the amylopectin ratio in the polysaccharide component increases.
[0056] The amylose / amylopectin ratio and molecular weight are controlled such that the polysaccharide component having F in Equation 1 is within the range to be described below can be effectively cross-linked to form a material having excellent absorption capacity and biodegradability.
[0057] In Equation 1, Ap and Am are ratios of amylopectin and amylose measured by the method described in "5. Measurement of contents of amylopectin and amylose in polysaccharide component" in the Example section of this specification, and the unit thereof is %.
[0058] In Equation 1, Mw is the weight average molecular weight of the polysaccharide component, which is a value measured by the method described in "4. Measurement of Molecular Weight of Polysaccharide Component" in the Example section of this specification, and its unit is g / mol.
[0059] The lower limit of F in Equation 1 may be about 4, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6, 5.8, 6.0, 6.2, 6.4, 6.6, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, or 8.2, and the upper limit thereof may be about 20, 18, 16, 14, 12, 10, 9, 8, 7, 6, or 5. F in Equation 1 may also be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits while being greater than or equal to, or greater than any of the above lower limits.
[0060] Within such a range, the polysaccharide component can be effectively cross-linked to form a polymer composition having excellent absorption capacity and biodegradability.
[0061] In Equation 1, the ranges of Mw, Am, and Ap can be adjusted to appropriate levels.
[0062] In one example, the lower limit of Mw in Equation 1 can be 200,000 g / mol, 250,000 g / mol, 300,000 g / mol, 350,000 g / mol, 400,000 g / mol, 450,000 g / mol, 500,000 g / mol, 550,000 g / mol, 600,000 g / mol, 650,000 g / mol, 700,000 g / mol, 750,000 g / mol, 800,000 g / mol, 850,000 g / mol, 900,000 g / mol, 950,000 g / mol, 1,000,000 g / mol, 1,500,000 g / mol, or 2,000,000 g / mol. 0g / mol, 2,000,000g / mol, 2,500,000g / mol, 3,000,000g / mol, 3,500,000g / mol, 4,000,000g / mol, 4,500,000g / mol, 5,000,000g / mol, 5,500,000g / mo l, 6,000,000g / mol, 6,500,000g / mol, 7,000,000g / mol, 7,500,000g / mol, 8,000,000g / mol, 8,500,000g / mol, 9,000,000g / mol, 9,500,000g / mol, 10, 000,000g / mol, 20,000,000g / mol, 30,000,000g / mol, 40,000,000g / mol, 50,000,000g / mol, 60,000,000g / mol, 70,000,000g / mol, 80,000,000g / mol, 90,000,000g / mol, 100,000,000g / mol, 110,000,000g / mol, 120,000,000g / mol, 130,000,000g / mol, 140,000,000g / mol, 150,000,000g / mol, 160,000 The upper limit thereof may be about 1,000 g / mol, 170,000,000 g / mol, or 180,000,000 g / mol, and the upper limit thereof may be 1,000,000,000 / mol, 900,000,000 / mol, 800,000,000 / mol, 700,000,000 / mol, 600,000,000 / mol, 500,000,000 / mol, 400,000,000 / mol, 300,000,000 / mol, 200,000,000 / mol, 150,000,000 / mol, 100,000,000 / mol, 90,000,000 / mol, 80,000,000 / mol, 70,000,000 / mol, 60,000,000 / mol, 50,000,000 / mol, 40,000,000 / mol, 30,0 00,000 / mol, 20,000,000 / mol, 10,000,000 / mol, 9,000,000 / mol, 8,000,000 / mol, 7,000,00 0 / mol, 6,000,000 / mol, 5,000,000 / mol, 4,000,000 / mol, 3,000,000 / mol, 2,000,000 / mol, 1,000,000 / mol, 900,000 / mol, 800,000 / mol, 700,000 / mol, 600,000 / mol, or 500,000 / mol. Mw may also be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. ,
[0063] The lower limit of Ap in Equation 1 may be about 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80%, and the upper limit thereof may be about 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 35%, or 20%. Ap may also be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0064] The lower limit of Am in Equation 1 may be about 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80%, and the upper limit thereof may be about 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 35%, or 20%. Am may also be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0065] In one example, the sum of the above Am and Ap in the polysaccharide component may be 100%.
[0066] In one example, when the polysaccharide of the polysaccharide component is a modified polysaccharide described below, the functional group introduced into the modified polysaccharide can be introduced into amylose or amylopectin, or can be introduced into both. The reaction of introducing the functional group described below can occur in both amylose and amylopectin, but when the content of amylopectin is greater than that of amylose, more effective modification is possible.
[0067] As the polysaccharide component, an appropriate type can be selected and used among the above-mentioned polysaccharides as long as it contains at least a polysaccharide containing amylose and amylopectin.
[0068] Combining one or two or more known polysaccharides to form a polysaccharide component such that F in Equation 1 is within the above range can be applied to the polymer composition.
[0069] Among known polysaccharides, starch can be typically used. When starch is used, starch having a gelatinization temperature in the range of about 50° C. to 90° C. and a peak viscosity (BU) in the range of 50 to 1000 can be used.
[0070] As the starch, any known starch may be applied without particular limitation, and for example, one or two or more types selected from potato starch, corn starch, rice starch, wheat starch, tapioca starch, and polymer starch may be applied.
[0071] Such polysaccharides may include at least two or more monosaccharide units connected by a covalent bond (e.g., a glycosidic bond). At this time, the monosaccharide unit may be exemplified by the above-mentioned biomolecules, and may be specifically exemplified by glucose, galactose, fructose, xylose, glucosamine, or N-acetylglucosamine, etc., but is not limited thereto.
[0072] Among the units contained in the polysaccharide, at least one may be a modified monosaccharide unit. The modified monosaccharide unit means a unit into which a functional group not existing in the original unit is introduced by chemical treatment.
[0073] A polysaccharide in which such modified polysaccharide units exist may be referred to as a modified polysaccharide.
[0074] The polysaccharide component may comprise a modified polysaccharide.
[0075] In one example, the functional group introduced into the modified monosaccharide unit body can be represented by, for example, the following Formula 1.
[0076] [Formula 1]
[0077]
[0078] In Formula 1, M1 is hydrogen or a metal, and when M1 is a metal, the O—M1 bond is an ionic bond.
[0079] The functional group of Formula 1 may be introduced into the unit body by bonding the oxygen atom on the left side of the above Formula 1 to the skeleton of the unit body.
[0080] In the functional group of Formula 1, the carbon-carbon double bond may exist in the polymer in a state in which the relevant double bond remains, or may exist in the polymer in a state in which the double bond participates in cross-linking.
[0081] In Formula 1, M1 is hydrogen or a metal. The type of the metal is not particularly limited, and it may generally be an alkali metal such as lithium, sodium, potassium or cesium.
[0082] In the polysaccharide, a functional group in which M1 in the above formula 1 is hydrogen and a functional group in which M1 is a metal may also coexist.
[0083] The functional group can be introduced by reacting the polysaccharide with an unsaturated dicarboxylic acid or its anhydride and replacing the hydroxyl group present in the unit body of the polymer with the functional group. Examples of dicarboxylic acids or their anhydrides can be exemplified by maleic acid or maleic anhydride, but are not limited thereto, and salts of maleic acid can also be applied.
[0084] The lower limit of the substitution rate of the functional group of the above formula 1 in the polysaccharide component can be about 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%, and the upper limit can be 300%, 295%, 290%, 285%, 280%, 275%, 270%, 265%, 260%, 255%, 250%, 245%, 240%, 235%, 230%, %, 225%, 220%, 215%, 210%, 205%, 200%, 195%, 190%, 185%, 180%, 175%, 170%, 165%, 160%, 155%, 150%, 145%, 140%, 135%, 130%, 125%, 120%, 115%, 110%, 105%, 100%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, or 40%. The substitution rate may also be in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. Within the range of the substitution ratio, cross-linking of the polysaccharide component can be efficiently performed, and physical properties (eg, absorption capacity and / or biodegradability, etc.) of the resulting polymer material can be stably ensured.
[0085] In the present specification, the substitution rate is a value indicating the degree to which the hydroxyl groups present in each unit body contained in the polysaccharide component are replaced by a predetermined functional group (for example, the functional group of the above formula 1), and is the average value of the degree of substitution of each unit body present in the polysaccharide. For example, if the unit body is a grape sugar (glucose) unit, there are three hydroxyl groups in the relevant unit before modification, and therefore, if all hydroxyl groups are replaced by the functional group of formula 1, the substitution rate of the relevant unit is 300%. However, the substitution rate of the polysaccharide is the average value of the degree of substitution of each unit present in the polysaccharide, so that, for example, when the substitution rates of each unit in a polysaccharide containing 5 grape sugar (glucose) units are 100%, 0%, 200%, 300% and 100%, the substitution rate of the polysaccharide is 140%, which is an average value. Such a substitution rate can be obtained by the polysaccharide. 1 H NMR analysis. That is, since the hydroxyl groups and substituted functional groups present in the polysaccharide can be 1 H NMR analysis can be used for quantification, so the substitution rate can be determined and, if necessary, the molecular weight of the polysaccharide before modification can be taken into account. 1The substitution rate was calculated from the results of H NMR analysis. 1 The method of quantitatively analyzing functional groups by H NMR analysis is known.
[0086] In one example, the unit body including the functional group of Formula 1 may be a unit body represented by Formula 2 below.
[0087] [Formula 2]
[0088]
[0089] In Formula 2, R1 is a hydroxyl group, an amino group or an alkylcarbonylamino group, L1 is an alkylene group or an alkylidene group, and M1 is hydrogen or a metal.
[0090] If M1 in Formula 2 is a metal, the O-M1 bond in Formula 2 may be an ionic bond.
[0091] The specific type of metal of M1 in Formula 2 is as described in Formula 1.
[0092] In Formula 2, specific types of the alkyl group, alkylene group or alkylidene group are the same as defined at the outset.
[0093] As described in Formula 1, the carbon-carbon double bond of the functional group in Formula 2 may exist in the polymer in a state where the double bond remains, or may exist in the polymer in a state where the double bond participates in cross-linking.
[0094] In the polymer, a functional group in which M1 in the above formula 2 is hydrogen and a functional group in which M1 is a metal may coexist.
[0095] In Formula 2, when R1 is a hydroxyl group, the unit body may generally be a case where it is derived from a so-called glucose unit body; when R1 is an amino group, the unit body may generally be a case where it is derived from a so-called glucosamine unit body; and when R1 is an alkylcarbonylamino group, the unit body may represent a case where it is derived from N-acetylglucosamine.
[0096] In one example, the functional group introduced into the modified monosaccharide unit may also be, for example, a functional group represented by the following Formula 3.
[0097] [Formula 3]
[0098]
[0099] In Formula 3, L2 is an alkylene group or an alkylidene group, M2 is hydrogen or a metal, and when M2 is a metal, the O-M2 bond is an ionic bond.
[0100] In Formula 3, specific types of the alkylene group or alkylidene group are the same as defined at the outset.
[0101] The functional group of Formula 3 may be introduced into the unit body when L2 on the left side in the above Formula 3 is bonded to the skeleton of the unit body.
[0102] In Formula 3, M2 is hydrogen or a metal. The type of the metal is not particularly limited, and it may generally be an alkali metal such as lithium, sodium, potassium or cesium.
[0103] In the polymer, a functional group in which M2 in the above formula 3 is hydrogen and a functional group in which M2 is a metal may coexist.
[0104] The functional group can be introduced by reacting the polysaccharide with an acetic acid chloride such as chloroacetate and substituting the hydroxyl group present in the unit body of the polymer with the functional group.
[0105] The lower limit of the substitution rate of the functional group of Formula 3 in the polysaccharide component can be about 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%, and the upper limit can be 300%, 295%, 290%, 285%, 280%, 275%, 270%, 265%, 260%, 255%, 250%, 245%, 240%, %, 235%, 230%, 225%, 220%, 215%, 210%, 205%, 200%, 195%, 190%, 185%, 180%, 175%, 170%, 165%, 160%, 155%, 150%, 145%, 140%, 135%, 130%, 125%, 120%, 115%, 110%, 105%, 100%, 95%, 90%, 85%, 80%, 75%, or 70%. The substitution rate may also be in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. When the functional group of Formula 3 is present, within the range of the substitution ratio, crosslinking of the polysaccharide component can be effectively performed, and physical properties (eg, absorption capacity and / or biodegradability, etc.) of the resulting polymer material can be stably ensured.
[0106] The definition of substitution rate is the same as that of the functional group in Formula 1, which can also be determined by the polysaccharide component. 1 Determined by HNMR analysis.
[0107] In one example, the unit body including the functional group of the above Formula 3 may be a unit body represented by the following Formula 4.
[0108] [Formula 4]
[0109]
[0110] In Formula 4, R2 is a hydroxyl group, an amino group or an alkylcarbonylamino group, L2 and L3 are each independently an alkylene group or an alkylidene group, and M2 is hydrogen or a metal.
[0111] When the above M2 is a metal, the O-M2 bond is an ionic bond.
[0112] The specific type of metal of M2 in Formula 4 is as described in Formula 3.
[0113] In Formula 4, specific types of the alkyl group, alkylene group or alkylidene group are the same as defined at the outset.
[0114] In polysaccharides, functional groups in which M2 in the above formula 4 is hydrogen and functional groups in which M2 is a metal may also coexist.
[0115] In the polysaccharide contained in the polymer composition, only one of the functional group of the above Formula 1 and the functional group of Formula 3 may be present, or both may be present at the same time.
[0116] Therefore, in the polysaccharide component of the polymer composition, either the unit body of the above formula 2 or the unit body of formula 4 may be present, or both may be present.
[0117] In one example, the polysaccharide can be included in the polymer composition in a cross-linked state. Therefore, the polymer composition may further include a cross-linking agent. However, if the cross-linking of the polymer composition is by self-cross-linking as described below, the polymer composition does not necessarily need to include a cross-linking agent.
[0118] In one example, the cross-linked state of the polysaccharide component may be a self-cross-linked state. The term "self-cross-linking" may mean a case where the polysaccharide in the polysaccharide component is cross-linked without applying a separate cross-linking agent, or a case where cross-linking is achieved using a minimal amount of a cross-linking agent.
[0119] By crosslinking in this manner, a polymer composition having both excellent absorption capacity and biodegradability can be provided. In general, polysaccharides have low crosslinking efficiency, so that effective crosslinking cannot be achieved even when crosslinking functional groups are introduced, but in the case of the present application, by applying the specific polysaccharide as described above, self-crosslinking can be effectively performed.
[0120] When the polysaccharide component is self-crosslinked, the upper limit of the weight ratio of the crosslinking agent relative to 100 parts by weight of the polysaccharide component in the polymer composition can be about 10 parts by weight, 9 parts by weight, 8 parts by weight, 7 parts by weight, 6 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, 2 parts by weight, 1 part by weight, 0.5 parts by weight, 0.1 parts by weight, 0.05 parts by weight, 0.01 parts by weight, 0.005 parts by weight, or about 0 parts by weight, and its lower limit can be about 0 parts by weight. The content can also be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The crosslinking achieved by using a crosslinking agent at the above ratio can also be considered as a crosslinking that falls within the scope of self-crosslinking.
[0121] The method for performing self-crosslinking is not particularly limited. Self-crosslinking can be performed, for example, in the presence of an oxidizing agent such as ammonium persulfate or other initiators.
[0122] For example, when the functional group of Formula 1 above is present in the polysaccharide component, crosslinking can be performed in the crosslinking environment as above by crosslinking or polymerization of the functional group of Formula 1 present in the polysaccharide, and by crosslinking or polymerization or grafting of free radicals generated by oxidation of the oxidant and the functional group of Formula 1 above.
[0123] In another example, crosslinking can also be performed using a crosslinking agent. In this case, as the crosslinking agent, a crosslinking agent used as a so-called internal crosslinking agent in the production of crosslinked polyacrylic acid generally used as a so-called SAP (super absorbent polymer) or a crosslinking agent used as an external crosslinking agent can be applied without any particular limitation, and both of the foregoing can also be applied.
[0124] As such a crosslinking agent, polyethylene glycol diacrylate, N,N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol (meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerol tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, ethylene glycol diglycidyl ether, propylene glycol, glycerol and / or ethylene carbonate and the like are known, and in the present application, if necessary, an appropriate crosslinking agent can be selected from the known crosslinking agents and used.
[0125] In order to perform more effective cross-linking and ensure desired physical properties, as a cross-linking agent, an organic acid having two or more carboxyl groups or an anhydride of the organic acid may be used in addition to the cross-linking agent.
[0126] When the cross-linking agent is used, ester bonds formed by reacting the carboxyl groups of the cross-linking agent with the hydroxyl groups in the polysaccharide component may be present in the polymer composition.
[0127] At this time, the type of organic acid is not particularly limited, but for example, an organic acid having a molecular weight (molar mass) in the range of about 90 g / mol to 300 g / mol or about 100 g / mol to 250 g / mol can be used. The lower limit of the number of carboxyl groups included in the organic acid can be about 2 or 3, and the upper limit can be about 10, 9, 8, 7, 6, 5, 4 or 3. The number of carboxyl groups can also be greater than or equal to or greater than the above-mentioned lower limit in the scope of any one; or less than or equal to or less than any one of the above-mentioned upper limits and greater than or equal to or greater than any one of the above-mentioned lower limits in the scope of any one.
[0128] Examples of such organic acids include, but are not limited to, citric acid, succinic acid, pimelic acid, and adipic acid. An organic acid or an anhydride thereof may be used as a crosslinking agent.
[0129] When the cross-linking agent is used, the upper limit of the weight ratio of the cross-linking agent relative to 100 parts by weight of the polysaccharide component can be about 10 parts by weight, 9 parts by weight, 8 parts by weight, 7 parts by weight, 6 parts by weight, 5 parts by weight, 4 parts by weight, or 3 parts by weight, and the lower limit thereof can be about 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, or 3 parts by weight. The content can also be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The content range of the cross-linking agent can also be a combination of any value in the above upper limits and any value in the above lower limits.
[0130] The polymer composition may also be subjected to additional treatments such as surface crosslinking treatment or grinding treatment, etc. In this case, the polymer composition may contain a polysaccharide component in a crosslinked state while in a particle form, or may contain a polysaccharide component in a crosslinked state and in a particle form while a surface crosslinking agent is coupled to the surface.
[0131] The polymer composition can be used in various applications by simultaneously exhibiting excellent absorbency and biodegradability.
[0132] For example, the polymer composition can be used as a sanitary product such as a diaper or sanitary napkin, or as an absorbent material for other applications requiring absorption. If necessary, the polymer composition can also be subjected to further crosslinking, surface treatment or physical grinding processes to improve the efficiency of being used as a sanitary product or absorbent material.
[0133] Therefore, the present application relates to absorbent materials or hygiene products (such as diapers, sanitary napkins, etc.) comprising the polymer composition.
[0134] A specific method of forming an absorbent material or a sanitary product by applying the polymer composition is not particularly limited, and for example, a method of forming an absorbent material or a sanitary product by applying an existing SAP may be used in the same manner.
[0135] Beneficial Effects
[0136] The present application can provide a polymer composition having excellent biodegradability and absorption capacity and use thereof. BRIEF DESCRIPTION OF THE DRAWINGS
[0137] Figures 1 to 5 To show the polysaccharide prepared in the preparation example 1 Graph of the H NMR analysis results. DETAILED DESCRIPTION
[0138] Hereinafter, the present application will be described in detail through Examples and Comparative Examples, but the scope of the present application is not limited to the following Examples.
[0139] 1. Evaluation of Centrifuge Retention Capacity (CRC)
[0140] Centrifugal retention capacity (CRC) is measured according to EDANA (European Disposables and Nonwovens Association) WSP 241.3. About 0.2g (W0) polymer composition is placed in nonwoven bag, sealed, then immersed in physiological saline solution. As physiological saline solution, the NaCl aqueous solution with a concentration of 0.9 % by weight is used. Keep this state about 30 minutes, use centrifuge to remove water 3 minutes under the condition of 250G from bag, and measure the quality (g, W2) of bag. The same operation is carried out to the identical nonwoven bag that does not comprise polymer composition, and quality (g, W1) is measured.
[0141] CRC(g / g) is calculated by substituting the measurement result into the following equation A.
[0142] The evaluation was performed under constant temperature and humidity conditions (23±1° C., relative humidity: 50±10%).
[0143] [Equation A]
[0144] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1
[0145] 2. Evaluation of Absorption Capacity Under Pressure (AUP)
[0146] The absorption capacity under pressure (AUP, 0.7psi) of polymer composition is measured according to the standard of EDANA (European Disposables and Nonwovens Association) WSP 242.3. A 400 mesh stainless steel wire mesh is installed at the bottom of a plastic cylinder with an inner diameter of about 60mm. Under the condition of a temperature of 23 ± 2°C and a relative humidity of 50%, about 0.90g (W0) of polymer composition is evenly spread on the wire mesh, and a piston capable of further evenly applying about 0.7psi load is installed thereon to make a measuring device. As a piston, a piston with an outer diameter slightly less than 60mm is used, and the piston is installed so that it can move up and down and will not form a gap with the inner wall of the cylinder. The weight (unit: g) (W3) of the measuring device is measured.
[0147] A glass filter having a diameter of about 90 mm and a thickness of about 5 mm is placed in a culture dish having a diameter of about 150 mm, and a physiological saline solution (NaCl aqueous solution having a concentration of 0.9 wt %) is applied to the same height as the upper surface of the glass filter. A filter paper having a diameter of about 90 mm is placed thereon. A measuring device is placed on the filter paper and the physiological saline solution is absorbed under a load of 0.7 psi for 1 hour. After 1 hour, the measuring device is raised and the weight W4 (g) is measured.
[0148] The absorption capacity under pressure (AUP) (g / g) was calculated by substituting each measured weight into the following equation B.
[0149] [Equation B]
[0150] AUP(g / g)=[W4(g)-W3(g)] / W0(g)
[0151] 3. Measurement of biodegradability
[0152] Biodegradability is measured in the manner specified in ISO 14855-1 (2005) standard. The above standard is a method for measuring the aerobic biodegradability of plastic materials under composting conditions, which is a method for calculating the biodegradability of polymer compositions by quantifying the amount of carbon dioxide released by the microorganisms that metabolize the relevant materials. When polymer compositions are applied to composting conditions according to this standard, biodegradability is measured for 6 months, and biodegradability is obtained as the ratio of the theoretical carbon dioxide production of the material and the actual carbon dioxide production. Here, theoretical carbon dioxide production and biodegradability are obtained according to equation C and equation D below, respectively.
[0153] [Equation C]
[0154] Theoretical carbon dioxide production (ThCO2, g / container) = M T O T ×C T O T ×(44 / 12)
[0155] In equation C, M T O T is the amount (g) of the total dry solid content of the test material (polymer composition) added to the compost at the beginning of the measurement, and C T O T It means the ratio of organic carbon contained in the total dry solid content of the test material (g / g).
[0156] [Equation D]
[0157] Biodegradability (%) = [{(CO2) T -(CO2) B} / ThCO2]×100
[0158] In equation D, (CO2) T is the cumulative amount of carbon dioxide produced from the compost container containing the test material (g / container), (CO2) B is the average value of the cumulative amount of carbon dioxide generated from the inoculum source container (g / container), and ThCO2 is the theoretical carbon dioxide generation determined in Equation C above.
[0159] 4. Molecular weight measurement of polysaccharide components
[0160] The molecular weight of the polysaccharide component was evaluated in the following manner.
[0161] (1) Preparation of mobile phase
[0162] Mobile phase A was prepared by filtering 1000 mL of a 150 mM NaNO 3 aqueous solution containing 0.02 wt % NaN 3 using a solvent purification system (Millipore Millisolve Kit, MilliporeSigma).
[0163] (2) Preparation of sample solution
[0164] The sample to be measured was collected in an amount of 25 mg and mixed with 5 mL of a 150 mM NaNO 3 aqueous solution containing 0.02 wt % NaN 3 , and then a sample solution was prepared by heating the mixture at 80° C. for 20 hours and then filtering it with a 0.4 μm nylon syringe filter.
[0165] (3) GPC (Gel Permeation Chromatography) / MALS (Multi-Anglue Light Scattering Detection) Conditions The molecular weight was evaluated using the sample solution and mobile phase A in the following manner.
[0166] Measuring instrument: Agilent GPC (Agilent 1200 series, USA)
[0167] Stationary phase: connected to Shodex OH-Pak 804 column and Shodex OH-Pak 80 column Mobile phase: A; 0.02% NaN3, 150mM NaNO3 aqueous solution = 100 (volume / volume%)
[0168] Flow rate: 0.4mL / min
[0169] Stationary phase temperature: 25°C
[0170] Injection volume: 100μl (0.45μm filtered)
[0171] Analysis time: 120 minutes
[0172] 5. Measurement of the content of amylopectin and amylose in polysaccharide components
[0173] The contents of amylopectin and amylose in the polysaccharide fraction were evaluated according to the method described in the paper (Potato Research 31 (1988) 241-246).
[0174] First, the sample was prepared by dissolving about 5 mg of polysaccharide (starch) in about 1 mL of sterile water (step 1), and heated to 95°C in a constant temperature water bath for about 15 minutes (step 2).
[0175] Subsequently, about 20 μl of the sample was placed in a cuvette (step 3), and about 980 μl of the iodine solution was added thereto and mixed (step 4).
[0176] Subsequently, the absorbance of the sample mixed with the iodine solution at wavelengths of 525 nm and 700 nm was measured and recorded respectively (step 5). The absorbance was measured using the OPTIZEN POP model of KLAB.
[0177] About 20 μl of water is placed in another cuvette, 980 μl of iodine solution is added thereto, and mixed (step 6). For the solution of step 6, the absorbance at wavelengths of 525 nm and 700 nm is measured and recorded in the same manner as in step 5, respectively (step 7).
[0178] The absorbance obtained in step 7 is subtracted from the absorbance obtained in step 5, and the ratio (%) of amylose is determined according to the following equation E (step 8).
[0179] [Equation E]
[0180]
[0181] In equation E, PA is the ratio of amylose (%), OD is 700 is the value obtained by subtracting the absorbance at a wavelength of 700 nm measured in step 7 from the absorbance at a wavelength of 700 nm measured in step 5, and OD 525 is a value obtained by subtracting the absorbance at a wavelength of 525 nm measured in step 7 from the absorbance at a wavelength of 525 nm measured in step 5.
[0182] Preparation Example 1.
[0183] Starch (Compound A) comprising a modified monosaccharide unit of the following formula A was prepared in the following manner. The modified monosaccharide unit of the following formula A is a monosaccharide unit into which a functional group derived from sodium acetate has been introduced.
[0184] [Formula A]
[0185]
[0186] As the starch material, a starch having a weight average molecular weight (Mw) of about 180,000,000 g / mol, an amylopectin ratio of about 81% and an amylose ratio of about 19% was used. The amylose ratio is a value determined by the above equation A, and the amylopectin ratio is a value obtained by subtracting the amylose ratio from 100%.
[0187] Starch, isopropanol (IPA) and NaOH aqueous solution (concentration: about 40%) are mixed in a 500mL RBF (round-bottom flask) and stirred at room temperature for about 20 minutes. The weight ratio of the mixture is set to 1:4:0.8 (starch: IPA: NaOH aqueous solution). Subsequently, about 80 parts by weight of sodium monochloroacetate are added thereto relative to 100 parts by weight of starch, the temperature is raised to 60°C, then stirred for about 1 hour, and the temperature is cooled to room temperature. After cooling to room temperature, the solvent is removed from the water, the reactant is dissolved in water, precipitated in methanol to remove water-soluble impurities, filtered to recover starch, and dried in a vacuum drying oven at 40°C for about 12 hours to obtain a solid target product (Compound A).
[0188] The substitution rate of the obtained target product (compound A) can be calculated by 1H NMR analysis was obtained using a Varian Unity Inova (500 MHz) spectrometer with a triple resonance 5 mm probe. 1 H NMR spectroscopy was performed at room temperature 1 HNMR analysis. 1 For H NMR analysis, a Bruker Avance Neo instrument was used.
[0189] Specifically, 50 mg of the obtained solid target product (Compound A) and 200 mg of a 30% D2DSO4 solution in D2O were mixed and stirred at 50°C for about 1 hour to initiate a hydrolysis reaction, and then the reaction was allowed to proceed. 1 H NMR analysis.
[0190] The target product (compound B) 1 The results of H NMR analysis are shown in Figure 1 The substitution rate determined by the above analysis is about 60%.
[0191] Preparation Example 2.
[0192] Modified starch was prepared in the same manner as in Preparation Example 1, except that starch having a weight average molecular weight (Mw) of about 12,000,000 g / mol, an amylopectin ratio of about 75%, and an amylose ratio of about 25% was used as starch.
[0193] The starch content was determined in the same manner as in Preparation Example 1. 1 H NMR results are consistent with the following Figure 2 The substitution rate determined from the results is about 60%.
[0194] Preparation Example 3.
[0195] Modified starch was prepared in the same manner as in Preparation Example 1, except that starch having a weight average molecular weight (Mw) of about 2,000,000 g / mol, an amylopectin ratio of about 69%, and an amylose ratio of about 31% was used as starch.
[0196] The starch content was determined in the same manner as in Preparation Example 1. 1 H NMR results and Figure 3 The substitution rate determined from the results is about 70%.
[0197] Preparation Example 4.
[0198] Modified starch was prepared in the same manner as in Preparation Example 1, except that starch having a weight average molecular weight (Mw) of about 920,000 g / mol, an amylopectin ratio of about 58%, and an amylose ratio of about 42% was used as starch.
[0199] The starch content was determined in the same manner as in Preparation Example 1. 1 H NMR results and Figure 4 The substitution rate determined from the results is about 52%.
[0200] Preparation Example 5.
[0201] Modified starch was prepared in the same manner as in Preparation Example 1, except that starch having a weight average molecular weight (Mw) of about 450,000 g / mol, an amylopectin ratio of about 19%, and an amylose ratio of about 81% was used as starch.
[0202] The starch content was determined in the same manner as in Preparation Example 1. 1 H NMR results and Figure 5 The substitution rate determined from the results is about 50%.
[0203] Preparation Example 6.
[0204] Modified starch was prepared in the same manner as in Preparation Example 1, except that starch having a weight average molecular weight (Mw) of about 140,000 g / mol, an amylopectin ratio of about 6%, and an amylose ratio of about 94% was used as starch.
[0205] As the starch was determined in the same manner as in Preparation Example 1 1 As a result of H NMR, the substitution rate was about 60%.
[0206] Example 1.
[0207] The starch prepared in Preparation Example 1 was dissolved in distilled water, and a crosslinking agent (citric acid) was added at a ratio of about 3 parts by weight relative to 100 parts by weight of the starch. It was stirred at room temperature for about 30 minutes, transferred to a steel pan, and dried in an oven at about 40° C. for about 12 hours. Subsequently, it was crosslinked for about 2 hours at a temperature of about 80° C. to prepare a desired polymer composition.
[0208] Example 2.
[0209] A polymer composition was prepared in the same manner as in Example 1, except that the starch prepared in Preparation Example 2 was used.
[0210] Example 3.
[0211] A polymer composition was prepared in the same manner as in Example 1, except that the starch prepared in Preparation Example 3 was used.
[0212] Example 4.
[0213] A polymer composition was prepared in the same manner as in Example 1, except that the starch prepared in Preparation Example 4 was used.
[0214] Example 5.
[0215] A polymer composition was prepared in the same manner as in Example 1, except that the starch prepared in Preparation Example 5 was used.
[0216] Comparative Example 1.
[0217] A polymer composition was prepared in the same manner as in Example 1, except that the starch prepared in Preparation Example 6 was used.
[0218] The Mw, Am and Ap values and F values in Equation 1 of the polymer compositions of Examples and Comparative Examples, and the CRC, AUP and biodegradability measured for each polymer composition are summarized and described in the following Table 1. In the following Table 1, the unit of Mw is ×1,000 g / mol.
[0219] [Table 1]
[0220]
[0221] From the results of Table 1, it can be determined that the polymer composition in which F in Equation 1 is 4 or more exhibits excellent absorption characteristics and biodegradability at the same time, while in the case of Comparative Example 1 in which F is 3.9, biodegradability is ensured but the absorption characteristics are significantly reduced.
Claims
1. A polymer composition comprising a polysaccharide component, wherein the polysaccharide component comprises amylose and amylopectin, wherein The polysaccharide component has F in the following equation 1 of 4 or greater: [Equation 1] in, Ap is the ratio of the amylopectin in the polysaccharide component, Am is the ratio of the amylose in the polysaccharide component, and Mw is the weight average molecular weight of the polysaccharide component.
2. The polymer composition according to claim 1, having a centrifuge retention capacity according to EDANA (European Disposables and Nonwovens Association) method WSP 241.3 of 12 g / g or more.
3. The polymer composition according to claim 1, having an absorption capacity under 0.7 psi pressure according to EDANA (European Disposables and Nonwovens Association) method WSP 242.3 of 1.5 g / g or more.
4. The polymer composition according to claim 1, which has a biodegradability of 60% or more. 5 . The polymer composition according to claim 1 , wherein the polysaccharide component comprises one or more selected from the group consisting of starch, dextrin and chitosan. 6 . The polymer composition of claim 1 , wherein Mw in Equation 1 is in the range of 200,000 g / mol to 1,000,000,000 / mol.
7. The polymer composition of claim 1, wherein Ap in Equation 1 is in the range of 5% to 95%.
8. The polymer composition according to claim 1, wherein the polysaccharide component has a polysaccharide containing a functional group of the following formula 1: [Formula 1] in, M1 is hydrogen or a metal, and when the above M1 is a metal, the O—M1 bond is an ionic bond, and the carbon-carbon double bond of Formula 1 may exist in a state of participating in cross-linking.
9. The polymer composition according to claim 1, wherein the polysaccharide component has a polysaccharide comprising a unit cell of the following formula 2: [Formula 2] in, M1 is hydrogen or a metal, and when the above M1 is a metal, the O-M1 bond is an ionic bond, and the carbon-carbon double bond of Formula 2 can exist in a state of participating in cross-linking, and R1 is a hydroxyl group, an amino group or an alkylcarbonylamino group, and L1 is an alkylene group or an alkylidene group.
10. The polymer composition according to claim 1, wherein the polysaccharide component has a polysaccharide containing a functional group of the following formula 3: [Formula 3] in, L2 is an alkylene group or an alkylidene group, M2 is hydrogen or a metal, and when the above M2 is a metal, the O-M2 bond is an ionic bond.
11. The polymer composition according to claim 1, wherein the polysaccharide component has a polysaccharide comprising a unit cell of the following formula 4: [Formula 4] in, R2 is hydroxyl, amino or alkylcarbonylamino, L2 and L3 are each independently an alkylene or alkylidene group, M2 is hydrogen or a metal, and when the above M2 is a metal, the O-M2 bond is an ionic bond.
12. The polymer composition of claim 1, wherein the polysaccharide component is cross-linked.
13. The polymer composition of claim 12, comprising ester bonds formed by reaction between hydroxyl groups of the polysaccharide component and a crosslinking agent. 14 . The polymer composition according to claim 12 , wherein the polysaccharide component is cross-linked with a cross-linking agent, and the cross-linking agent is an organic acid containing two or more carboxyl groups, or an anhydride of the organic acid. 15 . The polymer composition of claim 14 , wherein the organic acid has a molecular weight in the range of 90 to 300 g / mol and comprises 2 to 10 carboxyl groups.
16. The polymer composition of claim 14, wherein the crosslinking agent is citric acid, citric anhydride, pimelic acid, pimelic anhydride, adipic acid, adipic anhydride, succinic acid, or succinic anhydride. 17 . The polymer composition according to claim 14 , comprising 0.5 to 10 parts by weight of the cross-linking agent relative to 100 parts by weight of the polysaccharide component.
18. An absorbent material comprising the polymer composition according to any one of claims 1 to 17.
19. A hygiene article comprising the polymer composition according to any one of claims 1 to 17.
Citation Information
Patent Citations
Adhesive acrylate-olefin copolymers, methods for producing same and compositions utilizing same
KR1020220110608A